Canadian 24-h Movement Guidelines, Life Stress, and Self-Esteem Among Adolescents - Sampasa-Kanyinga, Hugues; Lien, Amanda; Hamilton, Hayley A.; Chaput, Jean-Philippe (Frontiers in Public Health, 2022)
Background Adolescence is often considered a period of heightened stress, and healthy active living behaviors may help those experiencing it to better cope with life stressors and increase their self-esteem. The 24-h movement guidelines for children and adolescents recommend ≥60 min per day of moderate-to-vigorous physical activity, ≤ 2-h per day of recreational screen time, and 9–11-h of sleep per night for school-aged children or 8–10-h per night for adolescents. The objective of this study was to examine the association of meeting the 24-h movement guidelines with life stress and self-esteem among students in Ontario, Canada. Methods Self-reported data on movement behaviors, life stress and self-esteem were derived from the 2019 cycle of the Ontario Student Drug Use and Health Survey, a cross-sectional and province-wide survey of students in grades 7–12 aged 11 to 20 years (N = 6,932). Multivariable ordered logistic regression analyses were adjusted for the complex sample design of the survey and for important covariates. Results Overall, meeting all combinations of movement behavior recommendations were associated with lower life stress and better self-esteem compared with meeting none of the recommendations, except meeting the physical activity only or screen time only recommendations that were not associated with lower life stress. Meeting all 3 recommendations was associated with lower life stress (OR: 0.40; 95 CI: 0.30–0.53) and better self-esteem (OR: 0.29; 95% CI: 0.21–0.40). There was a dose-response gradient between the number of recommendations met (3 > 2 > 1) and lower life stress (p < 0.001) and higher self-esteem (p < 0.001), with meeting all 3 recommendations being the best combination. Conclusions These findings suggest that meeting the recommendations of the 24-h movement guidelines is associated with lower life stress and better self-esteem among adolescents.